Pengaruh Kesesuaian Kompensasi Dan Efektivitas Pengendalian Internal Terhadap Kecenderungan Kecurangan Akuntansi - Luh Putu Ayu Rismayanti; Cokorda Gde Bayu Putra (Hita Akuntansi dan Keuangan, 2023)
The fact that accounting fraud is caused by several factors including weak internal control and inadequate compensation. The purpose of this study was to determine the effect of compensation and the effectiveness of internal control on accounting fraud. This research was conducted in village administrations in West Denpasar District. The number of samples taken was 31 respondents. The sampling technique used is saturated sampling, while the data analysis technique used is the descriptive test, classical assumption test consisting of normality test, multicollinearity, and heteroscedasticity test, instrument test consisting of validity and reliability test, test the right model that consists of coefficient of determination (adjusted R2), F test, and statistical test (t-test), and multiple linear regression analysis. The test results show that there is a positive and significant effect of Compensation Suitability on Accounting Fraud. Judging from the results of the t-test, the parameter coefficient value is 0.442 with a significance level of 0.001. There is a positive and significant effect on the Effectiveness of Internal Control on Accounting Fraud. Judging from the results of the t-test, the parameter coefficient value is 0.713 with a significance level of 0.000.